Expression profile of plasma microRNAs and target genes in patients with complicated pregnancy - D. G. Pashkovsky; E. V. Solovieva; Ts. R. Rabadanova; P. T. Gorbunova; A. B. Dubovaya; E. R. Muslimova; E. E. Khoroz; Z. S. Karabash; L. E. Sorokina (IRBIS LLC, 2023)
Aim: comparative analysis of the expression profile of plasma microRNAs and target genes in patients with complicated pregnancy.Materials and Methods. A prospective observational comparative study in parallel groups was carried out. The study included 73 women divided into three groups: the main group - 42 patients with preeclampsia (PE), the comparison group - 12 pregnant women with fetal growth retardation (FGR), the control group - 19 clinically healthy women with uncomplicated pregnancy. An examination was performed, which included the analysis of clinical characteristics and the study of microRNA expression in blood plasma using the real-time polymerase chain reaction.Results. MicroRNA hsa-miR-210-5p and hsa-miR-1972 were not identified in any plasma sample. Analyzing plasma microRNAs in group of women with PE showed significant changes in the expression levels of hsa-miR-517a-3p (p = 0.025), hsa-miR-517c-3p (p = 0.036), hsa-miR-574-5p (p = 0.015), hsa-miR-517a-3p (p < 0.001) and an increase in miR-20a-5p (p = 0.046) compared to control group. No significant differences were found in the miRNA expression profile in group of women with FGR compared to control group. Assessing an influence of the studied microRNAs on regulatory signaling pathways allowed to establish that hsa-miR-miR-146a-5p, -181a-5p, -210-3p, -517a-3p, -517c-3p, -574-3p, -574-5p, -1304-5p are potential regulators of the reaction cascades involved in the PE pathogenesis.Conclusion. The changes revealed in the circulating blood plasma miRNA level indicate the presence of specific transcriptomic alterations during complicated course of pregnancy.